TRAF3 Epigenetic Regulation Is Associated With Vascular Recurrence in Patients With Ischemic Stroke - Gallego-Fabrega, Cristina; Carrera, Caty; Reny, Jean-Luc; Fontana, Pierre; Slowik, Agnieszka; Pera, Joanna; Pezzini, Alessandro; Serrano-Heras, Gemma; Segura, Tomás; Martí-Fàbregas, Joan; Muiño, Elena; Cullell, Natalia; et al. (Stroke (1970), 2016)
BACKGROUND AND PURPOSE—Clopidogrel is one of the most used antiplatelet drugs in patients with cardiovascular disease. However, 16% to 50% of patients have a high on-clopidogrel platelet reactivity and an increased risk of ischemic events. The pathogenesis of high on-treatment platelet reactivity in patients with stroke is only partially explained by genetic variations. This study aims to find differentially methylated sites across the genome associated with vascular recurrence in ischemic stroke patients treated with clopidogrel. METHODS—From a cohort of 1900 patients with ischemic stroke, we selected 42 patients treated with clopidogrel, including 21 with a recurrent vascular event and 21 without vascular recurrence during the first year of follow-up. Over 480 000 DNA methylation sites were analyzed across the genome. Differentially methylated CpG sites were identified by nonparametric testing using R. Replication analysis was performed in a new cohort of 191 subjects and results were correlated with platelet reactivity in a subset of 90 subjects using light transmission aggregometry. RESULTS—A total of 73 differentially methylated CpG sites (P<1×10) were identified; 3 of them were selected for further replicationcg03548645 (P=1.42×10, TRAF3), cg09533145 (P=7.81×10, ADAMTS2), and cg15107336 (P=1.89×10, XRCC1). The cg03548645 CpG remained significant in the replication study (P=0.034), a deep analysis of this region revealed another methylation site associated with vascular recurrence, P=0.037. Lower cg03548645 (TRAF3) DNA methylation levels were correlated with an increased platelet aggregation (ρ=−0.29, P=0.0075). CONCLUSIONS—This study suggests for the first time that epigenetics may significantly contribute to the variability of clopidogrel response and recurrence of ischemic events in patients with stroke.